The response of soil nematode Caenorhabditis elegans on the sewage sludge-derived micropollutants - Čadková, Zuzana; Száková, Jiřina; Mukhtorova, Dilnora; Hlava, Jakub; Pulkrabová, Jana; Balík, Jiří; Tlustoš, Pavel; Vadlejch, Jaroslav (Journal of hazardous materials, 2020)
Sewage sludge application to soil is of great interest, due to required organic matter and the wide spectra of nutrients it provides. However, the presence of unpredictable content of emerging contaminants may turn this valuable raw material into a hazardous substance. In this study, three selected sewage sludges derived micropollutants from different origins; that is, one each under persistent organic pollutants (POPs), pharmaceuticals and personal care products (PPCPs) were considered. The effect of each micropollutant on the feeding activity of free-living soil nematode Caenorhabditis elegans was analysed. The analysis was performed in model soil solution using a larval feeding inhibition assay. The results showed no significant effects from selected POP-2,2',4,4',5-pentabromodiphenyl either and pharmaceutical-chlortetracycline on the feeding activity of tested nematodes. On the contrary, feeding activity was inhibited by PPCP-galaxolide (HHCB) with an effective concentration of 12.2 ± 2.2 mg.l-1. The calculated risk quotient for galaxolide (RQ = 0.14) demonstrated a medium ecological risk to the nematodes. Based on our findings, concentrations of micropollutants in sewage sludge treated soil pose negligible risk to feeding activity of soil nematode. However, the potential impact of musk compounds on free-living soil biota requires detailed evaluation in further research.
Keywords: Sewage; Animals; Caenorhabditis elegans; látky znečišťující životní prostředí; Environmental Pollutants; zvířata; testy toxicity; odpadní vody; Toxicity Tests